Budget travel mobile application / Nawariah Ahmad Zabidi - Ahmad Zabidi, Nawariah (2019)
Travel is the movement of people between distant geographical locations. Travel can be done by foot, bicycle, train, boat, bus, airplane, ship or, with or without luggage, and can be one way or round trip. Budget travel is travel that is budget-conscious. People usually want to travel but always tight on budget so they decided not to travel because they do not have enough money. This project is to develop an application budget travel mobile application. This mobile application is to help the travellers get an idea where to go and know the price before they go out. The method of interview and observation were used for collecting the requirements of this project. The research paper and articles also help to find more knowledge about the topic of this project. The methodology used in this project is Mobile Application Development Life Cycle (MADLC). It will describe and explain about the finding on the literature review, functional and non-functional requirements, and software tools used in develop the mobile application. As conclusion, the development of Budget Travel Mobile Application will give great opportunity to all people to plan ahead before travelling.